Choosing Herbal Toothpaste: Study on Consumer Behavior and Preferences in The Greater Jakarta Area - Septiani, Stevia; Indrawan, Dikky; Arista, Galih Saputra; Rakhmat, Asep; W Sari, Yessie; A Nuzulia, Nur; T Wahyuni, Wulan (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The research aims are investigating consumers’ psychology and behavioral characteristics and investigating the consumer’s characteristics that affects experienced preferences in the Greater Jakarta Area. Consumer profile and consumer behavior were carried out using descriptive statistics analysis and cross tabulation analysis. Meanwhile, to measure consumer preferences for herbal toothpastes, logistic regression analysis (logit) was used. This survey was conducted on 459 respondents in the Greater Jakarta area. The results of the analysis show that in general the customers of toothpaste products are women aged 25-44 years and have more than 3 family members. The majority of customers are well educated segments, work as private workers and belong to the SES A group. Based on cross tab analysis, it is known that gender (p value = 0.037) and age (p value = 0.025) have a significant correlation in choosing herbal toothpaste. These results were confirmed in the logit analysis where women prefer herbal toothpastes than men. Based on consumer psychological factors, most customers believe in buying toothpaste at offline stores, except for those who are under 30 years old. However, for consumers who live in DKI Jakarta, they prefer to buy toothpaste through online channels compared to those who live outside DKI Jakarta. Keywords: consumer behavior, consumer profile, herbal toothpastes, logistic regression